AN EMPIRICAL STUDY ON CONSEQUENCES FACED BY THE ADVOCATES IN THE ADMISSIBILITY OF FALSE EVIDENCE. - S.INDHU, Dr. K. KIRUBAGARAN (International Journal of Advanced Science and Technology, 2020)
An advocate is who represents another person’s interest. An advocate is a professional client who is an expert in the field of law and a Specialist lawyer who represent clients on a Court of law. The main objective of this paper is to study the duties of the advocate in the court, concept of admissibility of false evidence and to analyse the consequences faced by the advocate admissibility of false evidence. This study used simple random sampling method and 550 responses has been collected from the advocates of Chennai high court with information. This paper stated that the law in most of the powerful is based on the principle innocent until proven guilty. Legal profession is well privilege to profession in the world and lawyer must to engage to protect the rights liberties and interest in front of the judge.